Trascription in practice: nonstandard orthography. Issue 2 (25th August 2015) - Jaffe, Alexandra
Abstract : Transcriptions of spoken data are a central element of much applied linguistic research, serving both as the basis for large-scale corpora used by multiple analysts, and as one of the primary ways in which spoken data is presented in scholarly work. This article applies a political and ideological perspective to the analysis of a specific aspect of transcriptional practice that is seldom given much attention: the use of nonstandard orthography. While orthographic choices are often treated as neutral, transparent or trivial dimensions of applied linguistics transcripts, a review of the literature shows that nonstandard orthographies covertly attribute sociolinguistic stigma to those they represent. It goes on to explore in detail the sociolinguistic and pragmatic information value of nonstandard orthography in transcriptions, considering issues of predictability, consistency, intertextuality, and audience and readers' interpretive frameworks. The conclusions argue for recognition among applied linguists of the representational work done by nonstandard orthographies and hence, for very selective, principled and explicitly flagged uses of these spellings in academic corpora and transcripts.